Development of Novel Promiscuous Anti-Chemokine Peptibodies for Treating Autoimmunity and Inflammation - Abraham, Michal; Wald, Hanna; Vaizel-Ohayon, Dalit; Grabovsky, Valentin; Oren, Zohar; Karni, Arnon; Weiss, Lola; Galun, Eithan; Peled, Amnon; Eizenberg, Orly (Frontiers in Immunology, 2017)
Chemokines and their receptors play critical roles in the progression of autoimmunity and inflammation. Typically, multiple chemokines are involved in the development of these pathologies. Indeed, targeting single chemokines or chemokine receptors has failed to achieve significant clinical benefits in treating autoimmunity and inflammation. Moreover, the binding of host atypical chemokine receptors to multiple chemokines as well as the binding of chemokine binding proteins secreted by various pathogens can serve as a strategy for controlling inflammation. In this work, promiscuous chemokine binding peptides that could bind and inhibit multiple inflammatory chemokines, such as CCL2, CCL5, and CXCL9/10/11, were selected from phage display libraries. These peptides were cloned into human mutated immunoglobulin Fc-protein fusions (peptibodies). The peptibodies BKT120Fc and BKT130Fc inhibited the ability of inflammatory chemokines to induce the adhesion and migration of immune cells. Furthermore, BKT120Fc and BKT130Fc also showed a significant inhibition of disease progression in a variety of animal models for autoimmunity and inflammation. Developing a novel class of antagonists that can control the courses of diseases by selectively blocking multiple chemokines could be a novel way of generating effective therapeutics.